Robotic Knee Exoskeletons as Assistive and Gait Training Tools in Spina Bifida: A Pilot Study Showing Clinical Feasibility of Two Control Strategies - Taylor M. Devine; Afua Asante-Otoo; Katharine E. Alter; Diane L. Damiano; Thomas C. Bulea (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Robotic exoskeletons are increasingly available to children with movement disorders, most commonly cerebral palsy, as wearable aids to improve mobility, and as rehabilitation tools for gait training with the goal to improve walking when not wearing the device. The focus of this study was to design and evaluate a novel exoskeleton approach for children with crouch gait secondary to weakness caused by spina bifida. Two operational modes were tested: an assistive mode that aids knee extension during stance and late swing, and a gait training mode that assists knee extension in stance and resists it during late swing. These modes were evaluated in one participant with L4-5 myelomeningocele who completed a ten-visit study. Peak knee angle during midstance with and without the exoskeleton was evaluated during overground walking. Secondary outcomes included knee angle at initial contact, gait speed and vastus lateralis (VL) and semitendinosus (ST) electromyography (EMG). Exoskeleton assistance effectively increased knee extension in midstance (without device [left: $10.7\pm 4.7^{\circ }; right: 22.3\pm 4.0^{\circ }$ ]; with assistance [left: $- 9.5\pm 0.9^{\circ }; right: 4.1\pm 2.0^{\circ }$ ]). VL activity was significantly increased during periods of exoskeleton applied resistance, eliciting the desired effect with no change in gait speed at the final assessment. Interleaving assistance during stance with resistance during swing improved knee extension simultaneous with the desired EMG increases. Our results indicate overground exoskeleton use is safe and feasible as both a mobility aid and training tool in spina bifida. Further research at higher doses is warranted to evaluate the potential of these approaches in this clinical population.